Pembinaan Kelompok Pedagang Telur Asin Tegal “ Strategi Pemanfaatan Telur Asin Gagal Jual Menjadi Produk Kerupuk Telur Asin Aneka Rasa” - Sari Wiyanti; Ahmad Hanfan; Niken Wahyu Cahyaningtyas; Muhammad Siddik Erdi; Yustia Hapsari (Pusat Riset dan Inovasi Nasional, 2022)
This community service activity as a partner is a salted egg business group in the city of Tegal. This group is vulnerable to losses that are often experienced during the production process until the sale of salted eggs. This group only sells its product in the form of salted eggs without any product innovation. The losses experienced by partners were due to the product failing to sell due to cracked eggs during the boiling process. Another influencing factor is not having the creativity to use the failed product. PKM partners are also unable to see business opportunities by creating new high-value products from defective products. The purpose of this service program is to provide solutions to the problems experienced by partners. The result of this service is that partners can take advantage of defective salted egg products for various flavored salted egg crackers, make profit/loss reports, and make advertisements on social media